PROMOTION OF AN INNOVATIVE FOOD PRODUCT: ASPECTS OF THE TARGET MARKET - SAVYTSKA, NATALIIA; OLINICHENKO, KATERYNA; PRIADKO, OLHA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article presents the results of the analysis of market development in dynamics: the main trends in the market, factors of influence, development problems are identified. Analyzing, systematizing and summarizing the scientific works of many scientists, theoretical and applied aspects of marketing innovations, researches on the formation of consumer properties of food products have been considered. The markets of meat and meat products, sausages of Ukraine are analyzed. The main features of these markets, development trends and main drivers are identified. The peculiarities of consumer behavior in the market are studied, the main consumer tendencies are determined. In order to identify potential demand for innovative products, a marketing study was conducted, namely a survey of potential consumers using online technologies on the Google Forms platform and developed recommendations for the introduction of products on the market. In order to study the consumer market in Kharkiv, a questionnaire was developed, which consisted of interrelated, posed in a logical sequence of questions. The sample consisted of 300 respondents. The motives and criteria for choosing products of consumers of sausages of Ukraine are singled out. Criteria for consumer segmentation in the sausage market are proposed. The factors of supply and demand in the market of sausage products of Ukraine are determined. The competitive environment on the market is analyzed, the list of the most important producers of sausages of Ukraine is formed. Marketing tools for launching a new product based on the results of research of competitors and potential consumers have been developed, which contributes to the development of a successful concept of a new product in accordance with market needs and market conditions. The profile of the target audience and means of promotion of cooked sausage enriched with calcium on the market have been developed. According to the results of the study, conclusions were drawn, the investment attractiveness of the industry was studied.